The Poetic Image: Its Importance and Types (Journal of the College of Languages (JCL), 2014)
* The poetic image, especially the representation ones had got the attention of critics and learner in the West and the East; it became a cornerstone of poetry. This study concluded many of results, for example:- * The poetic image is the mainstay of the poetic text, and its technical transfer to the experience which Poet lived in, because he can portray by it all his emotions, inner feelings, and colorful sensations which are cleaning in the poetic text, through language formations, which provide us with beautiful and sensitive images. And it makes the reader of the poem ask his self, if he reading a poem, or watching theorist, views of existence? * The critical Viewes differed in the division of the image, depending on the sight which according to a researcher, writer, and scholars of literary, which is taken from, and influenced by, and perhaps the issue is still in the process of crystallization and diligence, because the topic and study about it is still new to the scholars and researchers critics. * The westerner critics meant about studying the patterns of the poem through the implications of various of the term, and the most important is the significance of mind , and the rhetorical and symbolic , affected by the curriculum , which relied on the application of the implications of the term and the concept. As well as a link to the image on the basis of rhetorical giveS indications of the different types of highly correlated ; due to the nature of these patterns pictorial autobiography, in view of modern rhetoric in particular. * Arab critics reported the studies that have been in the West for pictures of poem, and classified them, according to the efforts of the nature , utilize the curriculum of modern scientific disparate. So it has settled its opinion that the division patterns of the image in our critique of modern depends - affected by exchange-west - the remodeled according to the conventional implications. * I compaired the studies which have addressed the issue of patterns and I found that Dr. (Bushra), and Dr (Zaid al-Juhani) studies were closest to the accuracy of the study, as well as their awareness of the nature of the poetic image.